PENGETAHUAN SUPLEMENTASI KALSIUM SEBAGAI PREDIKTOR KEPATUHAN KONSUMSI PADA IBU HAMIL: STUDI CROSS-SECTIONAL DI KARAWANG - Rifka Alindawati; Ari Kurniasih; Rochmawati Rochmawati (Poltekkes Kemenkes Maluku, 2026)
Background: Preeclampsia is a major contributor to maternal mortality in Indonesia. WHO recommends a calcium intake of 1,500–2,000 mg/day for pregnant women with inadequate calcium consumption, which has been shown to reduce the risk of preeclampsia by up to 55%. The success of this intervention depends on the mother's compliance which is significantly influenced by her level of knowledge. Objective: To analyze the relationship between pregnant women's knowledge about calcium supplementation and compliance with calcium tablet consumption in the prevention of preeclampsia in the Tunggajati Health Center Working Area, Karawang Regency. Methods: Quantitative observational research with a cross-sectional design was conducted in December 2025–March 2026. A total of 92 pregnant women in the second and third trimester were involved through consecutive sampling techniques. Knowledge was measured using instruments based on the 2020 WHO guidelines (validity r = 0.412–0.786; reliability of Cronbach's α = 0.847), while adherence was measured using the Indonesian version of the Morisky Medication Adherence Scale-8 (MMAS-8) (α = 0.832). The Chi-square test along with the Prevalence Ratio (PR) was applied to the bivariate analysis, followed by multivariate logistic regression. Results: A total of 41.3% of respondents had good knowledge and only 35.9% achieved high compliance. A meaningful relationship was found between the two variables (p = 0.001; PR = 2.84; 95% CI: 1.71–4.72). After adjusting for confounding variables, knowledge remained an independent predictor (aOR = 4.12; 95% CI: 1.82–9.33; p = 0.001). Conclusion: Pregnant women's knowledge of calcium supplementation was proven to be an independent predictor of adherence to calcium tablet consumption. Strengthening antenatal education based on the Health Belief Model is recommended to increase compliance and support efforts to prevent preeclampsia.